Protective efficacy of monovalent and trivalent recombinant MVA-based vaccines against three encephalitic alphaviruses. Issue 34 (16th August 2018) - Hu, Wei-Gang; Steigerwald, Robin; Kalla, Marcus; Volkmann, Ariane; Noll, David; Nagata, Les P.
Abstract: The three encephalitic alphaviruses, western, eastern, and Venezuelan equine encephalitis viruses (WEEV, EEEV, and VEEV) are potential biothreat agents due to high infectivity through aerosol exposure, ease of production in large amounts, and relative stability in the environment. Currently, there is no licensed vaccine for human use to these three encephalitic alphaviruses, and efforts to move vaccine candidates forward into clinical trials have not been successful. In this study, the modified vaccinia Ankara-Bavarian Nordic (MVA-BN®) vaccine platform was used to construct and produce three monovalent recombinant MVA-BN-based encephalitic alphavirus vaccines, MVA-BN-W, MVA-BN-E, and MVA-BN-V. Additionally, a MVA-BN-based construct was designed to produce antigens against all three alphaviruses, the trivalent vaccine MVA-BN-WEV. The protective efficacy of these vaccines was evaluated in vivo . Female BALB/c mice were immunized with two doses of each monovalent MVA-BN-based alphavirus vaccine, a mixture of the three monovalent vaccines, MVA-BN-W + E + V, or the trivalent vaccine MVA-BN-WEV at a four-week interval. Two weeks after the booster immunization, the mice were instilled intranasally with 5 × 10 3 to 1 × 10 4 plaque forming units of WEEV, EEEV, or VEEV. All mice immunized with monovalent vaccines survived the respective virus challenge without any signs of illness or weight loss, while all the control mice died. The triple mixture of vaccines or the trivalent vaccine also provided 90 to 100% protection to the mice against WEEV and VEEV challenges, and 60% to 90% protection against EEEV challenge. These data suggest that each monovalent MVA-BN-W, MVA-BN-E, and MVA-BN-V is a potential vaccine candidate against respective encephalitic alphavirus and the three monovalent vaccines can be given in a mixture (MVA-BN-W + E + V) or the trivalent vaccine MVA-BN-WEV can serve as a true multivalent vaccine without significantly reducing efficacy against WEEV and VEEV despite slightly reduced efficacy against EEEV challenge.